Efficiency of Sliding Plans in a Linear Model with Time-Dependent Technology - Kaganovich, Mikhail (Review of Economic Studies, 1985)
A procedure of sliding planning is considered in a simple dynamic model of Leontief type. At every step of this procedure, a long-term plan is generated starting from a current state of the economy for a future time interval of a fixed finite length (a “forecast horizon”), but only a decision concerning the first year is implemented. Proceeding from the attained state, the next step is carried out. Matrices of input-output coefficients are assumed to vary within uniform bounds. Provided that the forecast horizon is sufficiently long, the resulting sliding planning path is proved to be in a certain sense approximately optimal.